The Educational Quality Development Model of Kaoru Isikawa's Perspective - Moh. Vito Miftahul Munif (STAI Terpadu Yogyakarta, 2024)
This study aims to describe how the concept of developing quality education from Kaoru Ishikawa's perspective. This research uses a qualitative descriptive approach in the form of library research. The analysis technique used is content analysis. The results of this study show: 1) Quality Control can be done with the concept of quality circle, namely plan-do-check-action (PDCA) as a quality control tool that can ensure the quality of educational institutions. 2) The quality control circle concept is a design that cuts across all areas of quality improvement including the integration of quality assurance in new product development. In this way, the quality control circle potentially represents the majority of dialogue points for implementing Total Quality Control (TQC) or Company-Wide Quality Control (CWQC) in educational institutions. 3) The concept of Cause and Effect Diagram is a diagram that serves to solve problems effectively by putting the problem into a matrix of causal relationships to solve problems in educational institutions comprehensively.